Bleeding After Right Laparoscopic Adrenalectomy - Yelfimov, Daniel A. (Society of Laparoendoscopic Surgeons, 2010)
The current standard of care for treating benign adrenal disease is laparoscopic adrenalectomy. Surgical tools, such as ultrasonic shears and vessel sealing systems, have increased in popularity and improved surgical outcomes. However, the safety profile of clipless and sutureless adrenalectomy has not been completely established. We report on a complicated 74-year-old male who underwent significant postoperative hemorrhage following laparoscopic adrenalectomy. Interventional radiology with renal artery stent insertion was successful for the management of postoperative bleeding in this high-risk patient.